Does the consumption of soya products affect cholesterol levels, blood pressure, or other cardiovascular health indicators? - Walendzik, Aleksandra; Racisz, Kinga; Duda, Joanna; Kędzia, Jakub; Obcowska, Alicja; Racisz, Paweł; Sencerek, Łukasz (Quality in Sport, 2025)
Introduction and Purpose Cardiovascular diseases (CVD) are the leading factor of mortality among people in the world. For this reason, people are trying to find factors that could improve the condition of the circulatory system. Soy is one of the most popular products in Asian cuisine. Its consumption is increasing due to a strong interest in vegetarian cuisine, in which soy is an important element. As its popularity grows, more and more research is being done to see if it has cardiovascular disease-preventing properties. Aim of the study This study aims to analyse the current state of knowledge regarding the effect of soy consumption on: hypertension, lipid profile, biomarkers of inflammation, vascular epithelium and impact on mortality caused by cardiovascular diseases. Material and methods For this review, we analyzed articles that we found in Pubmed and Google Scholar and that were related to our topic. Conclusion Many studies have shown a beneficial effect of soy products on lipid profile, especially in lowering LDL-C levels. Soy consumption may have an impact on modulating inflammatory markers, but further research is needed. Researchers have shown that soy may have a role in lowering blood pressure, especially in people with hypertension or an increased risk of CVD. Soy can be a part of our daily, healthy diet, but its impact on all-cause mortality and CVD depends on many factors such as people’s age, comorbidity, dietary context and type of consumed soy ( e.g. fermented or not fermented).